KOMPARASI TAFSIR KITAB KLASIK DAN TAFSIR DIGITAL BERBASIS CHATGPT TENTANG FENOMENA DEMONSTRASI - Subhan, Subhan (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Abstract: This article examines the phenomenon of demonstrations from the perspective of the Qur’an by comparing classical exegesis with digital interpretation based on ChatGPT. The ease of access to Qur’anic exegesis through web platforms and artificial intelligence (AI) raises critical questions regarding its validity: does it conform to the interpretative standards established by scholars, or does it still require verification through primary tafsir sources? This study aims to explore the similarities and differences between classical and digital interpretations when applied to the theme of demonstrations. Employing a qualitative method with a library research approach, the study utilizes Tafsir al-Ṭabarī, Tafsir Ibn Kathīr, and digital responses generated by ChatGPT. The findings indicate that classical exegesis emphasizes Islamic normative principles such as amar ma‘rūf nahi munkar (enjoining good and forbidding evil), the prohibition of fasād (corruption), justice, and consultation. Demonstrations are deemed permissible if conducted peacefully to uphold justice but are prohibited if they lead to anarchy and disorder. Meanwhile, ChatGPT provides interpretations in a popular, communicative, and contextual style, making them more accessible to the public. In conclusion, both approaches converge in substance allowing peaceful demonstrations while rejecting anarchic actions but differ in their mode of presentation: classical tafsir is textual-normative, whereas digital tafsir is more practical and contextual. These findings highlight the importance of integrating both approaches in addressing contemporary socio-religious dynamics. Keywords: Tafsīr al-Ṭabarī, Tafsīr Ibn Kathīr, ChatGPT, demonstrations